Cognitive, social, emotional, and moral development of fourth-grade elementary school students - Sutranda Anang Daud; Rahmad Mohulaingo; Sri Wanda Limbanadi; Intan Lasri Sasmita; Regita Halid; Mia Usman; Mila Karnila Lawani; Irvin Novita Arifin; Isnanto (Penelitian Ilmu Pengetahuan Sosial, 2026)
Background: Elementary school is a crucial stage for students’ cognitive, social, emotional, and moral development, as these domains form the foundation for lifelong learning and character formation. Understanding students’ developmental characteristics is essential for designing learning environments that support holistic growth. This study aims to identify the developmental characteristics of fourth-grade students at SDN 1 Suwawa Selatan and analyze how the school environment facilitates their overall development. Methods: This study employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with the fourth-grade homeroom teacher, and documentation of students’ academic and non-academic activities during the 2025 academic year. The collected data were analyzed descriptively to identify patterns related to students’ developmental characteristics and supporting educational practices. Findings: The findings show that fourth-grade students demonstrate considerable progress in logical thinking, problem-solving, and language skills, consistent with the concrete operational stage of development. Social development is reflected in improved collaboration, communication, and participation in group activities, although some students still require support in emotional regulation and conflict resolution. Emotional development is characterized by increased self-confidence and responsibility toward learning tasks, while moral development is evident through compliance with school rules, respect for teachers, and active involvement in character education programs. Furthermore, teacher-centered and student-centered learning strategies, a positive classroom climate, interactive learning activities, cooperative learning models, contextual teaching approaches, and parental involvement significantly contribute to students’ holistic development. Conclusion: Fourth-grade students at SDN 1 Suwawa Selatan exhibit balanced development across cognitive, social, emotional, and moral domains. Sustained collaboration among teachers, parents, and school administrators is essential to provide a supportive learning environment that promotes optimal academic achievement and socio-emotional development. Novelty/Originality of this article: This study provides an integrated qualitative analysis of elementary students’ cognitive, social, emotional, and moral development within a single educational setting while highlighting the combined influence of instructional strategies, classroom climate, and parental involvement on students’ holistic development.